Impact of a Literacy Program on the Academic Performance of First-Year University Students in Chile [Impact D’Un Programme D’Alphabétisation Sur la Performance Scolaire Des Étudiants de Première Année D’Université Au Chili] [Impacto de Un Programa de Lectoescritura en Elrendimiento Académico de Estudiantes de Primer Año Universitario en Chile] - Urzua-Martinez, S (Universidad de Antioquia, 2021)
In the last decade, higher education institutions have deployed a series of programs to teach reading and writing at this educational level; however, little is known about the effect of these initiatives on student academic performance. The objective of this study was to determine the effects of one of these iniciatives on the academic performance of first-year Psychology students studying at the regional branches of Concepción, Santiago, Puerto Montt and Valdivia from the San Sebastián University, in Chile. The program was designed so that it would associate learning with the production and analysis of texts typical of the students’ disciplinary field. To estimate the effect of the program, a sample of the work done by 644 students who entered the institution in 2016 and 2017 was analyzed. Through a multiple regression model, which incorporated sociode-mographic and socio-educational variables, previous academic performance, cognitive skills, study strategies and contextual variables, it was concluded that participation in the program had a positive and statistically significant effect on students’ academic performance. The findings confirm the importance of teaching reading and writing as a situated process, especially during the first years of university. © 2021